The Global Demography of Aging: Facts, Explanations, Future - David E. Bloom; Dara Lee Luca (Institute for the Study of Labor (IZA), 2016)
Population ageing is the 21st century's dominant demographic phenomenon. Declining fertility, increasing longevity, and the progression of large-sized cohorts to the older ages are causing elder shares to rise throughout the world. The phenomenon of population ageing, which is unprecedented in human history, brings with it sweeping changes in population needs and capacities, with potentially significant implications for employment, savings, consumption, economic growth, asset values, and fiscal balance. This chapter provides a broad overview of the global demography of aging. It reviews patterns, trends, and projections involving various indicators of population aging and their demographic antecedents and sequelae. The chapter also reviews theories economists use to explain the behavioral changes driving the most prominent demographic shifts. Finally, it discusses the changing nature of aging, the future of longevity, and associated policy implications, highlighting some key research issues that require further examination.
Keywords: J11; J14; N30; 330; population aging; economic demography; longevity